High Gain Metamaterial Implemented Antenna Design with Circular Polarization for mm-Wave 5G and 6G Sub-THz Communication - Khan, Aafreen; Ahmad, Anwar; Alam, Maksud (Journal of Electronics and Informatics, 2024)
A high-gain metamaterial-enabled circularly polarized antenna has been proposed. Two patch structures patch A and patch B have been designed by using different shape slots. After slot etching on the patch, two different metamaterial techniques were used. Circular metamaterial (MTM) was implemented for Patch A, while rectangular MTM was used for Patch B. The implementation of MTM resulted in increased antenna gain, as well as improvements in impedance bandwidth RL and AR. So, in the proposed article two antenna structures ANT-A and ANT-B, are presented. The maximum gain achieved for ANT-A is 34.759dBi, covering the frequency bands (28.997-202.113) GHz, and (205.884-336.693) while in the case of ANT-B, it is 36.3155dBi, covering the frequency bands (29.178-330.490) GHz, and (334.936-336.702) GHz. The proposed antenna structure is a useful design for mm-wave 5G and 6G Sub-THz communications.